Correlation between serum cartilage oligomeric matrix protein and major adverse cardiovascular events within 30 days in patients with acute coronary syndrome - Chen, Hao (Ann Transl Med, 2021)
BACKGROUND: We studied the correlation between cartilage oligomeric matrix protein (COMP) and major adverse cardiovascular events in patients with acute coronary syndrome (ACS) within 30 days. METHODS: This study included 170 ACS patients who were hospitalized in the Second Affiliated Hospital of Nantong University from August 2017 to April 2019. Serum COMP level was measured at baseline. The enrolled patients were followed up for 30 days and grouped according to the occurrence of major adverse cardiovascular events (MACE) during follow-up. Among the 170 patients, 23 patients had MACE during hospitalization (MACE group), and 147 patients had no MACE (no MACE group). RESULTS: The serum COMP levels in the MACE group were significantly higher than those of the non-MACE group [84.85 (51.55, 141.75) vs. 20.65 (9.11, 46.31) ng/mL, respectively, P<0.05]. The area under the receiver operating characteristic (ROC) curve for COMP in predicting the occurrence of MACE within 30 days was 0.839, with a cutoff level of 39.9 ng/mL [95% confidence interval (CI): 0.774–0.890], 86.96% sensitivity, and 72.79% specificity (P<0.0001). Multivariate logistic regression analysis showed that serum COMP could be used as an independent predictor of MACE within 30 days in ACS patients [odds ratio (OR): 1.024, 95% CI: 1.0133–1.0349, P=0.0001]. CONCLUSIONS: Serum COMP is associated with the short-term prognosis of ACS patients. High serum COMP levels can be used as a predictor of MACE within 30 days in ACS patients.